Does becaplermin (platelet-derived growth factor-BB) reverse detrimental effects of ischemia on colonic anastomosis? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
Purpose: The aim of this study was to evaluate the effects of becaplermin on normal and ischemic colon anastomoses. Methods: Forty adult male Wistar-Albino rats were divided into four equal groups of ten. AD rats underwent standard left colon resection and end-to end anastomosis. The groups were as follows: Group 1, normal anastomosis alone; Group 2, ischemic anastomosis alone; Group 3, normal anastomosis and becaplermin therapy, and Group 4, ischemic anastomosis and becaplermin therapy. All animals were killed on postoperative Day 4. Intra-abdominal adhesions were scored, and anastomotic healing was evaluated with both in situ bursting pressure and hydroxyproline levels. Results: According to bursting pressure results, there was a significant difference between Group 2 and Group 4 (P<0.05), but there was no statistically significant difference between Group 1 and Group 3 (P>0.05). Hydroxyproline values revealed no statistically significant difference among any of the groups (P>0.05). With regard to intra-abdominal adhesion scores, Group 3 had significantly lower values than Group 2 and Group 4 (P<0.05). No statistically significant difference was observed between the other groups. Conclusions: Detrimental effects of ischemia on colonic anastomotic healing were reversed with becaplermin therapy. However there was no such benefit on nonischemic anastomoses. Intra-abdominal application of this gel did not lead to an increase in intra-abdominal adhesion formation.
Keywords: becaplermin; Regranex; colon; anastomosis; ischemia; DIABETIC ULCERS; GASTROINTESTINAL-TRACT; DOUBLE-BLIND; RHPDGF-BB; GEL; TENSION; OXYGEN; SAFETY